Off with their heads! Copyright infringement in the Canadian online higher educational environment - Kelly Edmonds (The Canadian Network for Innovation in Education (CNIE), 2006)
Issues of copyright infringement are contentious for academia in the online environment. The educational community on campus must carefully consider how digital materials are used, created and disseminated online given that present laws that regulate these actions are not well developed. It can seem like anyone's guess on how to proceed in order to avoid copyright infringement. This paper offers current descriptions of intellectual property, copyright laws, infringements, and plagiarism in a Canadian context with a view on creating, using and disseminating digital works. The impact of copyright infringement on students and faculty in higher education is explored and some suggestions are made for protective practice.